2005
DOI: 10.1111/j.1439-0426.2005.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of spawning of bluefin tuna (Thunnus thynnus L., 1758) and the tuna species (Auxis rochei Ris., 1810, Euthynnus alletteratus Raf., 1810) in the eastern Mediterranean Sea: preliminary results of TUNALEV larval survey in 2004

Abstract: Further evidence of spawning of bluefin tuna (Thunnus thynnus L., 1758) and the tuna species (Auxis rochei Ris., 1810, Euthynnus alletteratus Raf., 1810) in the eastern Mediterranean Sea: preliminary results of TUNALEV larval survey in 2004 Summary A tuna larval survey (TUNALEV) in the Northern Levantine Basin (Cilician Basin) was conducted onboard a trawler from 5 to 18 June 2004. To determine the spatial distribution and abundance of tuna larvae, Bongo 60 and Bongo 90 nets were used. Ichtyoplankton samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 3 publications
9
26
0
Order By: Relevance
“…For example, a 1994 larval survey of the entire Mediterranean collected 1160 tuna larvae, including 183 BFT, none of which were caught in the Levantine Sea (Piccinetti et al 1997). These results are not surprisingly, since the survey was conducted between 21 June and 7 July, several weeks after the established spawning season (Karakulak et al 2004) and south of Cyprus, instead of in the Bays of Antalya and Mersin, north of the island, where BFT larvae are often found (Oray and Karakulak 2005). Japanese surveys have reported low densities of BFT larvae in hauls taken in the mid-Levantine Sea around the Herodotus Basin (Tsuji et al 1997, Nishida et al 1998).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…For example, a 1994 larval survey of the entire Mediterranean collected 1160 tuna larvae, including 183 BFT, none of which were caught in the Levantine Sea (Piccinetti et al 1997). These results are not surprisingly, since the survey was conducted between 21 June and 7 July, several weeks after the established spawning season (Karakulak et al 2004) and south of Cyprus, instead of in the Bays of Antalya and Mersin, north of the island, where BFT larvae are often found (Oray and Karakulak 2005). Japanese surveys have reported low densities of BFT larvae in hauls taken in the mid-Levantine Sea around the Herodotus Basin (Tsuji et al 1997, Nishida et al 1998).…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, most larval surveys conducted in the Levantine Sea have used nets with a 1 mm mesh size which are unlikely to retain the entire smaller size fraction of larvae (Oray and Karakulak 2005). Therefore, it is currently inadvisable to compare the results of larval surveys taking place in the eastern Mediterranean with other locations, since they cannot be considered as quantitative hauls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larvae of the same species, except the Atlantic bonito, have also been collected in other areas of Tunisian waters (Koched et al 2012, 2013, 2015, Zarrad et al 2013) and in the central and eastern part of the Mediterranean (Garcia et al 2005, Tsuji et al 1997, Oray and Karakulak 2005.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have demonstrated that Tunisian waters constitute a potential spawning area for several tuna species, like other Mediterranean areas, such as the Balearic archipelago (Garcia et al 2003, Alemany et al 2010, Piccinetti et al 2013, the Tyrrhenian Sea (Cavallaro et al 1997, Piccinetti et al 1997, the Ionian Sea (Tsuji et al 1997, Santamaria et al 2000, Piccinetti et al 2013 and the eastern Mediterranean (Somarakis et al 2011, Oray and Karakulak 2005, Isari et al 2008.…”
Section: Introductionmentioning
confidence: 99%